2022
DOI: 10.1002/smll.202106442
|View full text |Cite
|
Sign up to set email alerts
|

To Be or Not to Be – Review of Electrical Bistability Mechanisms in Polymer Memory Devices

Abstract: Organic memory devices are a rapidly evolving field with much improvement in device performance, fabrication, and application. But the reports have been disparate in terms of the material behavior and the switching mechanisms in the devices. And, despite the advantages, the lack of agreement in regards to the switching behavior of the memory devices is the biggest challenge that the field must overcome to mature as a commercial competitor. This lack of consensus has been the motivation of this work wherein var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 190 publications
0
19
0
1
Order By: Relevance
“…With the increasing demand on ultrahigh-density data-storage (UHDDS) systems in advanced information processors and flexible electronics, the prospect of adopting organic materials as memory medium in UHDDS semiconductors has aroused more attention. Organic materials afford attractive merits of low cost, easy processing, excellent miniaturization potential, and few environmental footprints as compared to inorganic electronics. In addition, organic memory materials hold promise to realize UHDDS since their structures can be tuned at the molecular level to induce multiple resistive switching characteristics. Attributed to their structural adjustability and scalability, not surprisingly, organic molecules have been demonstrated as promising materials for high-performance semiconductors such as organic photovoltaics, , organic field-effect transistors, , organic light-emitting diodes, , and organic batteries. , Their application in organic resistive random-access memory (ReRAM) is currently also under progress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing demand on ultrahigh-density data-storage (UHDDS) systems in advanced information processors and flexible electronics, the prospect of adopting organic materials as memory medium in UHDDS semiconductors has aroused more attention. Organic materials afford attractive merits of low cost, easy processing, excellent miniaturization potential, and few environmental footprints as compared to inorganic electronics. In addition, organic memory materials hold promise to realize UHDDS since their structures can be tuned at the molecular level to induce multiple resistive switching characteristics. Attributed to their structural adjustability and scalability, not surprisingly, organic molecules have been demonstrated as promising materials for high-performance semiconductors such as organic photovoltaics, , organic field-effect transistors, , organic light-emitting diodes, , and organic batteries. , Their application in organic resistive random-access memory (ReRAM) is currently also under progress.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of organic materials including polymers, ,, small molecules, and organic–inorganic hybrid compounds have been used as electroactive elements in ReRAM devices. Especially, the resistances of some metal/organic/metal structured memory devices can be effectively adjustable through molecular engineering, leading to multilevel data storage. ,, However, the probable instability of organic active compounds under high voltages often causes device degradation and/or failure during long-term operation. , Another challenge faced by organic-based ReRAM is the non-ideal resistive switching because of the inferior intrinsic conductivity of organic molecules .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, organic resistive switching memory (ORSM) based on organic materials possesses unique merits, such as compatibility with large-area solution processing, mechanical flexibility, possibility of multilevel storage, and easy modulation by molecular design and synthesis strategy. It has been reported that single-component organic molecule, , multicomponent organic molecules, , and organic–inorganic hybrid materials , present resistive switching effect through charge transfer, trapping, conformation change, redox reaction, and filamentary conduction. Particularly, the multicomponent organic molecules consisting of small molecule and polymer has been used as the active layer of high-performance ORSM, whose crystallization and phase separation can be restrain .…”
Section: Introductionmentioning
confidence: 99%
“…Resistive random access memory (RRAM) is highly popular, owing to its high write and erase speeds, high storage density, and multi-level storage; additionally, it is considered the most potential candidate for next-generation memory [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Several studies have reported the excellent performance of RRAM, such as MoS 2 filament transistors with high on/off ratio (2.6 × 10 9 ), power-efficient h-BN memories, and cellulose memories with a significant on/off ratio (10 6 ) and low SET/RESET voltages (<0.5 V) [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%